Новогодняя сказка: [стихи : для чтения родителями детям] / Ирина Гурина - Гурина Ирина Валерьевна (Фламинго, 2007)
Экземпляры: ДБ (20121217) / Инвентарный номер: 41290zzzzz / Цена: 40.00 / Сис.шифр: 84(2) / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2=Рус)